Beatrice and Virgil - Martel, Yann (High Street, Edinburgh : Canongate Books Ltd, 2010)
In a tale exploring the limitations of language in understanding and describing the Holocaust, a novelist and a taxidermist collaborate on a play about a donkey and a howler monkey who have survived a genocide.
Keywords: Authors -- Fiction; Taxidermists -- Fiction; Animals -- Fiction